Impact of calcined bauxite aggregates on the polishing resistance and skid resistance performance of SMA-7 asphalt mixtures - Pengfei Li; Lingkun Kong; Nan Mao; Chenwei Gu (PLoS ONE, 2025)
High-performance anti-skid asphalt mixtures are essential for improving skid resistance and pavement durability. This study investigates the skid resistance performance of small-aggregate-size SMA-7 asphalt mixtures using calcined bauxite (CB) aggregates. Four types of aggregates—75#, 85#, and 88# CB and limestone—were used in the mixture preparation. Various laboratory tests, including pavement performance, Polished Stone Value (PSV) of aggregates, three-wheel polishing, and dynamic friction tests, were conducted to evaluate the performance and friction characteristics of the mixtures at various polishing stages. The results indicate that the optimal coarse-to-fine aggregate ratio for SMA-7 is 75:25, with a maximum particle size of 6.35 mm. The PSV of 88# CB aggregate stabilizes after 120,000 polishing cycles, exhibiting a decay rate 30% slower than that of limestone aggregates. Among the mixtures, 88#CB-SMA demonstrates superior high-temperature stability (1.5 times higher than limestone), slightly better low-temperature crack resistance, and significantly enhanced polishing resistance. Additionally, the dynamic friction coefficients of CB mixtures show slower attenuation, retaining 29.4–36.3% higher residual friction compared to limestone even after prolonged polishing. Strong correlations (R2 > 0.85) between the attenuation rates of PSV and dynamic friction coefficients confirm that the enhanced wear resistance of CB aggregates is key to long-term skid resistance, particularly at lower speeds. These findings suggest that high-grade CB aggregates greatly improve both the skid resistance and overall performance of asphalt mixtures, providing valuable insights for designing durable small-size asphalt wear layers.